Оптимізація ресурсного потенціалу комунального підприємства водопостачання - Тімофєєв, В. О.; Чуб, О. І. (ХНУРЕ, 2016)
The analysis of the characteristics and functions of housing and utilities sector of Ukraine, in particular, the state of water and sanitation utilities has been performed. Obtained are components of utilities resource potential. We consider the formulation of a multicriterial resource scheduling problem of repair departments of utilities as a problem of optimal placement. The reduction technique of the multicriterial problem to a set of one-criterion problems has been proposed.
Keywords: житлово-комунальне господарство; ЖКГ; водопровідно-каналізаційне господарство; ВКГ; ремонтно-будівельні організації; РБО; витрати енергоресурсів; управлінські інновації; планування ресурсного потенціалу; ресурсний потенціал